2021
DOI: 10.1111/ppl.13331
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of hydraulic failure and cell vitality explains tree capacity to recover from drought

Abstract: Global climatic models predict an increment in the frequency and intensity of drought events, which have important consequences on forest dieback. However, the mechanisms leading to tree mortality under drought conditions and the physiological thresholds for recovery are not totally understood yet. This study aimed to identify what are the key physiological traits that determine the tree capacity to recover from drought. Individuals of a conifer (Pseudotsuga menziesii M.) and an angiosperm (Prunus lusitanica L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 65 publications
4
60
0
Order By: Relevance
“…It means that this threshold was below the death tipping point for E. camaldulensis saplings in our growth conditions. This is in line with observations in beech and poplar saplings (Barigah et al 2013a;Barigah et al 2013b), pine (Hammond et al 2019;Mantova et al 2021) and lavender (Lamacque et al 2020). Furthermore, we observed that the occurrence of embolism in our study was not random at the onset of embolism and at moderate levels of PLC but related to the vessel diameter distribution pattern within the xylem as previously underlined in poplar (Cai & Tyree 2010;Lemaire et al 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It means that this threshold was below the death tipping point for E. camaldulensis saplings in our growth conditions. This is in line with observations in beech and poplar saplings (Barigah et al 2013a;Barigah et al 2013b), pine (Hammond et al 2019;Mantova et al 2021) and lavender (Lamacque et al 2020). Furthermore, we observed that the occurrence of embolism in our study was not random at the onset of embolism and at moderate levels of PLC but related to the vessel diameter distribution pattern within the xylem as previously underlined in poplar (Cai & Tyree 2010;Lemaire et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, a xylem percentage loss of conductance (PLC) of approx. 88% has been linked to death in some angiosperms (Barigah et al 2013b;Lamacque et al 2020;Mantova et al 2021;Urli et al 2013), whereas PLC values of approx. 80% have been proposed as a critical threshold for some conifer species (Hammond et al 2019;Mantova et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that the high proximity of the incipient mortality threshold to the turgor loss point could be due to variability among individuals, which could shift the incipient mortality threshold in population‐level mortality curves (Martinez‐Vilalta et al, 2019). If so, the onset of mortality risk at the individual level might be slightly further away from turgor loss (Mantova, Menezes‐Silva, Badel, Cochard, & Torres‐Ruiz, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In all RCM-type models previously published, the apoplasmic and symplasmic compartments are not separated, which limits the possibility of explicitly simulating the water content of living tissues. However, living tissue water content is likely to be a key factor in organ and plant mortality (Martinez-Vilalta et al 2019;Mantova et al 2021). In SurEau, the specific description of symplasmic and apoplasmic capacitance and resistances between symplasm and apoplasm would allow further understanding of how water transfer fluxes between these compartments can improve survival.…”
Section: Comparison With Other Modelling Approachmentioning
confidence: 99%